Lanthanide-Doped Luminescent Nanomaterials From Fundamentals to Bioapplications - Chen, Xueyuan; Liu, Yongsheng; Tu, Datao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Lanthanide-Doped Luminescent Nanomaterials reviews the latest advances in the development of lanthanide-doped luminescent inorganic nanoparticles for potential bioapplications. This book covers the chemical and physical fundamentals of these nanoparticles, such as the controlled synthesis methodology, surface modification chemistry, optical physics, and their promising applications in diverse bioassays, with an emphasis on heterogeneous and homogeneous in-vitro biodetection of tumor biomarkers. This book is intended for those readers who are interested in systematically understanding the materials design strategy, optical behavior of lanthanide ions, and practical bioapplications of lanthanide nanoparticles. It primarily focuses on the interdisciplinary frontiers in chemistry, physics and biological aspects of luminescent nanomaterials. All chapters were written by scientists active in this field and for a broad audience, providing both beginners and advanced researchers with comprehensive information on the subject. Xueyuan Chen is a Professor at Fujian Institute of Research on the Structure of Matter (FJIRSM), Chinese Academy of Sciences. Yongsheng Liu is a Research Associate Professor at FJIRSM, Chinese Academy of Sciences. Datao Tu is a Research Assistant Professor at FJIRSM, Chinese Academy of Sciences.
A General Introduction to Lanthanide Ions -- Size Effect on the Luminescence of Lanthanide Ions in Nanoparticles -- Controlled Synthesis of Lanthanide-Doped Nanoparticles -- Surface Modification Chemistry of Lanthanide-Doped Nanoparticles -- Optical Spectroscopy of Lanthanide-Doped Nanoparticles -- In-Vitro Luminescent Biodetection Based on Lanthanide-Doped Nanoprobes -- Bioimaging Based on Lanthanide-Doped Nanoprobes -- Multimodal Biosensing Based on Lanthanide-Doped Nano-Bioprobes -- Concluding Remarks and Perspectives.
Keywords: Nanochemistry; Biomedical engineering; Optical materials; Materials Science; Optical and Electronic Materials; Biomedical Engineering; Nanochemistry; Optics, Optoelectronics, Plasmonics and Optical Devices